Prarancangan Pabrik Cumen dari Propilen dan Benzena dengan Proses Q-Max Kapasitas 100.000 Ton/Tahun - Septiana, Norma, Eni Budiyati, S.T, M.Eng, Kusmiyati, S.T, M.T, Ph.D (2017)
Cumene (C9H12) is a material used for the manufacture of phenol and acetone. Cumene is produced using q-max process which is carried out in a fixed bed muktitubes reactor with cooling dowtherm A and proceed on a gas-gas phase with -2000 catalyst. The reaction is exothermic with the operating conditions at a temperature of 350-393,06oC with pressure 25 atm. This product is cumene with 99,68% purity. Steps ocess includes the preparation of raw materials, the formation of cumene in the reactor, and purification products. rification of the product is done in the distillation tower. Cumene plant requires raw materials, such as propylene at 35.557 ton/year, benzene 64.976 amounted to 4.036,22 ton/year. Supporting units of this plant includes water, steam, compressed air, electricity and fuel units. this plant also is supported laboratory quality control of raw materials and products with the specifications is expected. In addition there is a sewage treatment units which handles solid, liquid, or gas waste from the production process.Form of this corporate is a limited liability company with a line and staff organizational structure. The system is based on the division of employee working hours which consisted of employee shift and non-shift.Cumene plant is planned to stand in 2020 in the area of Banten, West Java. Fixed capital investment (FCI) of this plant is Rp 84.275.630.804, and amount of working capital (WC) is Rp 136.590.330.539. From the economic analysis it can be shown that the Percent return on investment (ROI) before taxes is 53,35% and ROI after tax is 40,05%. Pay out time (POT) before tax is 1,58 years, while after tax is 2,00 years. Break even point (BEP) is 44,38%. The amount of shut down point (SDP) is 28,74%, and the discounted cash flow (DCF) is 49,88%. From the results of the economic analysis of cumene plant from propylene and benzene with Q-max process is feasible to set up in Indonesia.